Microsoft Expression Web 4 in depth - Cheshire, Jim (--in depth., 2011)
Offers instructions on creating dynamic Web content with Microsoft Express Web 4, covering such topics as creating content, using frames, publishing a site, creating style sheets, using form controls, and using PHP--